Application of research-based jurisprudence inquiry learning to students' critical thinking skills - Sitompul, Hamela Sari; Simangunsong, Anita Debora; Situmorang, Idawati (Institute of Computer Science (IOCS), 2025)
Students find it difficult to compete in the 21st century job market or do not yet have skills in the job market, but companies are having a hard time finding employees. The lack of programs to train critical thinking, so students are less willing to ask questions, more to take notes and memorize. Indonesia's golden age in 2045 is expected to be transformed into a developed country. Therefore, the learning concept must improve critical thinking skills, creativity, innovation and collaboration. The purpose of this study is to improve students' skills in critical thinking and build student and community collaboration. The research method used is a quasi experiment with a nonequivalent pretest-posttest control group design. The research sample was regular class A as the experimental class and regular class B as the control class with 15 students each through purposive sampling. The test instrument consisted of an essay test adjusted to the critical thinking indicators. The results of the study were analyzed using a t-test which obtained a 2-tailed sig value (0.00) <? (0.05) so that H1 was accepted, meaning that there was an influence of the Research-Based Jurisprudence Inquiry model on students' critical thinking skills.